Efektivitas Edukasi Stunting dengan Media Whatsapp terhadap Tingkat Pengetahuan Orang Tua yang Memiliki Balita Stunting - Ni Kadek Briggita Brillianti; Ida Erni Sipahutar; I Nyoman Ribek (Jurnal Gema Keperawatan, 2022)
Stunting is a condition in which children under five have a length or height that is less than their age. One of the contributing factors is knowledge. This study aims to determine the effectiveness of stunting education with whatsApp media on the level of knowledge of parents who have stunting children under five in Payangan sub district in 2022. This research used one group pretest-post test design and random sampling technique with 40 people as the sample. Knowledge data collection using a questionnaire. Statistical test using computerized, normality test using shapiro-wilk and nonparametric test using wilcoxon test (95% CI =0.05). The results obtained before the sample received stunting education, group discussions, and leaflet distribution, there were nine people (22,5%) who had sufficient knowledge and 31 people (77,5%) with less knowledge before the interventions in the form of education, group discussions, and leaflet distribution. Meanwhile after the interventions there were 40 people (100%) who had good knowledge. The result of the Wilcoxon Test is p value 0.000, it means that there is a significant increase in sample knowledge after education, group discussions, and leaflet distribution. Therefore, stunting education with whatsApp media is effective on the level of knowledge of parents who have stunting children under five in Payangan sub district in 2022. Recommendations: it is expected that parents of children under five more actively seek information through health workers or electronic media and discussions with health workers via whatsApp.